Rechargeable scalp massager brush / Nur Bazilah Fatini Mohd Azmi ... [et al.]. - Mohd Azmi, Nur Bazilah Fatini; Mohd Ariffin, Nur Ainin Sofia; Abd Manap, Siti Sarah Asyiqin; Anuar, Nur Aini Syahirah; Mohamad Norizan, Nur Nadzlinda (2024)
Brief description of the business and product concepts: BrushCraft & Co. addresses the growing trend of personal hair care with its innovative Rechargeable Scalp Massager Brush, a revolutionary tool that improves upon traditional scalp massager brush. Some of the features of our Rechargeable Scalp Massager Brush are detachable scalp massager brush, built-in shampoo dispenser, USB socket, speed control button and on-off button. The brush is made up from soft, silicon bristle, detachable and able to vibrate for massage effects. Apart from that, there is a built-in shampoo dispenser at the handle of the brush. Next, there is a speed and on-off button at the side of the brush. There is also a USB socket at the side of those two buttons. By addressing limitations of manual scalp massager brush such as inconsistent pressure and movement, BrushCraft & Co. offers a unique and satisfying hair care experience, elevating hair care routines to a new level by promoting healthy hair and scalp. Target market and projections: Our target market is young adults between the ages of 19 and 25. Young adults are generally comfortable with technology and are attracted to hair care tools that offer convenience and multi-functionality. The rechargeable aspect eliminates the need for batteries, while the built-in shampoo dispenser saves time and effort during hair washing. The brush might be particularly attractive to young adults with specific hair concerns like dandruff, oily scalp, or hair loss, as the massaging action and increased blood flow could potentially offer benefits in these areas. Social media platforms like Instagram, Twitter, and TikTok are used to sell our product. By promoting our product on those platforms, we can reach a large audience, including people all over the world.